Pengembangan Media Pembelajaran Berbasis Aplikasi Tiktok pada Materi Larutan Penyangga dengan Menggunakan Model PBL (Problem Based Learning) Untuk Meningkatkan Motivasi Belajar Siswa SMA - Adinda Salsabila; Harizon Harizon; Wilda Syahri; Firdiawan Ekaputra; Isra Miharti (Ridwan Institute, 2026)
The social media platform that is currently popular among teenagers is TikTok.This application allows users to upload short videos with various themes including education. Students' motivation to learn can increase through the use of video learning media, especially on the TikTok platform which is popular and attractive to today's digital generation. This study aims to find out the process of developing TikTok-based learning media using the Problem Based Learning (PBL) model on buffer solution materials to determine the feasibility of media developed based on material experts, media experts, practitioners as well as student responses and the impact on student motivation. The development of TikTok application-based learning media uses the Problem Based Learning (PBL) model using the 4D development model (Define, Design, Develop, and Disseminate). The research instruments used are in the form of interview guidesheets, questionnaires, documentation. The data analysis techniques used are qualitative data analysis and quantitative data analysis. The results of this study show that the use of learning media has a positive impact on students' learning motivation with a questionnaire score of 88% (very good category). From the feasibility aspect, the media was declared very valid based on the assessment of material experts and media experts with a percentage of 100%, as well as the validation of instructional design with an average score of 4.00. The results of the practicality test showed a student response of 89.0% (excellent category), which confirms that this learning media is practical, easily accessible, and in accordance with the characteristics of high school students as the digital generation. Based on the development process and research results, it is concluded that the development of TikTok application-based learning media using the Problem Based Learning (PBL) model on the buffer solution material is feasible to be used theoretically and practically as one of the teaching materials on the buffer line and has the potential to increase student learning motivation based on expert opinions and teacher assessments.